ENT Manifestations of Tuberculosis: An Important Aspect of ENT Practice - Umair Hafeez, Muhammad Nadeem, Ayesha Shafi, Aysha Nauman, Zafar Iqbal, Muhammad Ashraf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Extra pulmonary tuberculosis is the type of TB that affects organs other than the lungs. Cervical lymphadenopathy, acute otitis media, laryngitis, pharyngitis, and nasal TB are the most common ENT presentations. Objective: The aim of the study was to explore the ENT manifestations of tuberculosis. Methodology: The current study was conducted at the Department of ENT, M. Islam Teaching Hospital Gujranwala from 1st February 2022 to 31st July 2022. A total of 197 individuals who visited the department’s outpatient clinic were checked for possible ENT symptoms of tuberculosis. To determine the degree of involvement of the ear, nose, and throat, a thorough ENT history was taken from each patient. A radiological evaluation of the cervical spine, soft tissue neck, and Schuler’s view X-ray for mastoid cysts were performed, direct laryngoscopy, diagnostic nasal endoscopy, and otoendoscopy were carried out. A fine needle aspiration cytology (FNAC) and ultrasound neck examination were conducted. USG and CT were used for diagnosing the deep neck space abscess. The collected data was input into spreadsheets and subjected to analysis using Microsoft Excel 2010 and chi-square analysis was employed. P values that were statistically significant were those that were less than 0.05. Results: Out of 197 tuberculosis patients only 124(63%) individuals diagnosed with ENT manifestations of TB. Out of which male were 71(57.25%) and female were 53 (42.74%). Majority of them of them were in the 36–60 age range 70(56.45%). In the Ear, nose and throat region, TB of lymphadenopathy has been identified to be the most prevalent lesion 102(82.25%). The most typical manifestations were shown to be fever 54 (43.54%). alcohol consumption and smoking were the risk factors. 66 percent of the patients did not have any risk factors. There was no correlation seen between smoking or alcohol and any particular TB lesions. Pulmonary tuberculosis was the most prevalent co-morbidity20.9%) while 79(63.7%) of the participants showing no co-existing disease. Conclusion: The percentage of extra pulmonary TB in the current study was 63%. The most typical presentation in the head and neck area remains TB lymphadenitis Keywords: ENT; Manifestations: Tuberculosis